If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5a + 6) = 2(3a + 8) Reorder the terms: 2(6 + 5a) = 2(3a + 8) (6 * 2 + 5a * 2) = 2(3a + 8) (12 + 10a) = 2(3a + 8) Reorder the terms: 12 + 10a = 2(8 + 3a) 12 + 10a = (8 * 2 + 3a * 2) 12 + 10a = (16 + 6a) Solving 12 + 10a = 16 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 12 + 10a + -6a = 16 + 6a + -6a Combine like terms: 10a + -6a = 4a 12 + 4a = 16 + 6a + -6a Combine like terms: 6a + -6a = 0 12 + 4a = 16 + 0 12 + 4a = 16 Add '-12' to each side of the equation. 12 + -12 + 4a = 16 + -12 Combine like terms: 12 + -12 = 0 0 + 4a = 16 + -12 4a = 16 + -12 Combine like terms: 16 + -12 = 4 4a = 4 Divide each side by '4'. a = 1 Simplifying a = 1
| -2(4b+3)=-8b-7 | | 7(8+9C)= | | 50+4y=130 | | 2(4-1.3x)-4.1x=0.5 | | 6-9x+10c^2= | | -266=-7(8m-2) | | 4x+5=-x+8+5x-3 | | 3f+g=-14 | | x-6+7=26(x+7) | | 7*8-6+3=47 | | S+k+m=180 | | -2x(x+4)+6=-3 | | (3a+7)+(2a-6)=(-9) | | 2(-5+v)=-4 | | v^2+14v=19 | | -8=-6x-3 | | 17=w | | 12=4+6m | | G(x)=3f(x-2)-4 | | 7T+2=12+5T | | 12=10x+2x | | -2(6n-8)=16-12n | | 4k+7=-4 | | 7K+-8K+-5K= | | 8x-2=-9+nx | | x-.55x=0 | | 1=-15+8x | | 12=1.5 | | 2(3x-5)=9-(2x-5) | | 0.2x-6=x | | 2(5d+3)=4d | | -5.6+12.2=5h |